A formação da Escola de Educação Popular Fulidaidai-Slulu em Timor-Leste: uma história de resistência - Urban, Samuel Penteado (Universidade Federal de São Carlos, 2016)
Timor - Leste has been considered the first democracy to establish in the XXI century. Timor - Leste’s past was marked by invasions, which resulted in c omplex Education today. This complexity has been materialized through the language issue in the country. At first, the proc ess of Portuguese colonization did very little to Education in Timor. T he Indonesian invasion in 1975, after the short period of independence, it was up invested in the construction of schools, from kindergarten to higher education, based on an integrationist ideological and oppressive education. In contrast, internally the struggle for restoration of independence agains t the Indone sian invasion, the F ront of Timor - Leste Independent (FRETILIN), together Union of Timores Students (UNETIM ) and members of the group called House of Timor es, began a process of Popular E ducation , which had great influ ence of Paulo Freire, Mao Tse - Tung and Amilcar Cabral. This Popular Education a political awareness and based on everyday know ledge of the learners. It is a contextualized education to the fight needs Maubere Pedagogy ) . After the restoration of independence in 2002, the main struggle of farmers in the district of Ermera has been focused on the issue of land rig hts. In other words, the struggle for agrarian reform is a historical result of all the past economic exploitation of the land. In this sense, the fight against illiteracy and other n eeds related to agriculture to the Union of Ermera Farmers (UNAER) through the formation of Fulidaidai - Slulu School. This education is based in a local economy concept called Fulidaidai - Slulu and can be translated from Makalero and Mambai languages as working together or even work in solidarity - an alternative to capitalism economy. The aim of this study is to understand which the concept of this education in the formation of the School of Education Fulidaidai - Slulu Popular, considering it as a historical res ult of Education started in mid - 1974 ( fight agains t illiteracy and obscurantism). T he formation of this school the subject of this research. The methodological procedures of the research are inserted in his general appearance is know n as qualitative resear ch, with this also the character of a participant observation. Thus, as data collection, we carried out a literature review and semi - structured interviews to those involved in the formation of Popular Education School Fuli daidai - Slulu in Timor - Leste - in o rder to understand the f ormation of this school. Therefore, the design of this education in the School of Education Fulidaidai - Slulu Popular, at first has been main influences: Paulo F reire, Amilcar Cabral and Mao Tsé - Tung; secondly, Borja da Costa, Ablili o Araujo, Vicente Maria Reis (Sahe), Dr. Lekdoe and Dr. Maubere. In this sense, the M au bere P edagogy practices have led to the selection of the Fulidaidai School ad content, apted to current "epochal unity." Thus, it was possible to carry out this research starting from an experiment in International C ooperation in the formation of the School of Education Fulidaidai - Slulu Popular (Teacher Training Program in Portuguese Language - PQLP )
The formation of the popular education school Fulidaidai-Slulu in Timor-Leste: a resistance story
Keywords: Educação popular; Popular education; Timor Leste; East Timor; Economia alternativa; Solidary Economy; Economia Fulidaidai-Slulu; Fulidaidai-Slulu Economy; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO::SOCIOLOGIA DA EDUCACAO